Kabbala und religiöse Identität: Eine religionswissenschaftliche Analyse des deutschsprachigen Kabbalah Centre - Bauer, Nicole Maria (transcript, 2017)
Despite the progression of secularisation, new religious groups are enjoying great success, and attract hundreds of people a year with the use of a range of marketing strategies. But what is it, exactly, that makes them attractive? Nicole Maria Bauer's religious studies analysis of the Kabbalah Centre provides one answer to that question. The Kabbalah Centre is a neoreligious movement founded at the end of the 1960s in the USA which has been active in Germany for several years, and which draws people from a range of different religious contexts. This transdisciplinary study examines constructions of religious identity on an institutional and personal level, and outlines a new approach for their investigation. The book also takes up current trends such as 'religious branding' and connects them with newer approaches from identity research.